Methodological characteristics and future directions for plyometric jump training research: A scoping review update - Ramirez-Campillo, R.; Moran, J.; Chaabene, H.; Granacher, U.; Behm, D. G.; Garcia-Hermoso, A.; Izquierdo, M. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The aim of this scoping review was i) to update a previous review on the main methodological characteristics and shortcomings in the plyometric jump training (PJT) literature, and ii) to recommend, in light of the identified methodological gaps, future research perspectives. We searched four electronic databases. From 6,128 potentially relevant articles, 420 were considered eligible for inclusion. As an update of a previous review, this represents an increase of ~200 articles, illustrating that this field of research is growing fast. However, the relative "quality" or shortcomings were similar when compared to the preceding scoping review. In the current article, the main identified shortcomings were an insufficient number of studies conducted with females, individual sports, and high-level athletes (~22%, ~7%, and ~14% of overall studies, respectively); insufficient description of training prescription (~54% of studies); and studies missing an active/passive control group and a randomised group allocation process (~37% and ~24% of overall studies, respectively). Furthermore, PJT was often combined with other training methods and added to the participants` regular training routines (~50% and ~35% of overall studies, respectively). The main outcomes of this scoping review urge researchers to conduct PJT studies of high methodological quality (e.g., randomised controlled trials) to get trustworthy evidence-based knowledge. In addition, owing to the limited research conducted with females, individual sports, and high-level athletes, more studies are needed to substantiate the available findings. Finally, the identification of cohort-specific PJT dose-response relations which elicit optimal training effects still need to be identified, particularly in the long term.